2021
DOI: 10.1017/s0034670521000139
|View full text |Cite
|
Sign up to set email alerts
|

Adam Smith on Impartial Patriotism

Abstract: Scholars have emphasized Adam Smith's critique of the dangers of patriotism, but have not paid close attention to its potential value. This article recovers from Smith's work an attractive model of patriotism without nationalism. The potential value of patriotism lies in inspiring individuals to realize an ideal of impartial beneficence, which consists in overcoming selfishness and other subpolity partialities and in promoting the greater happiness of all fellow citizens. Smith defends virtuous patriotism agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In describing self-preference (SP), Elazar [49] revealed that when people transcend innate self-preference to act justly, they perceive themselves as "but one of the many". Veljkovic et al [50] conclude that personal preferences more significantly impact entrepreneurship than other professions.…”
Section: Entrepreneur Self-esteem and Gpsmentioning
confidence: 99%
“…In describing self-preference (SP), Elazar [49] revealed that when people transcend innate self-preference to act justly, they perceive themselves as "but one of the many". Veljkovic et al [50] conclude that personal preferences more significantly impact entrepreneurship than other professions.…”
Section: Entrepreneur Self-esteem and Gpsmentioning
confidence: 99%